Dietary diversity and associated factors among children aged 6–23 months attending a public health hospital in Awi zone, Ethiopia, 2023 - Mulatu, Sileshi; Ejigu, Lemessa Jira; Dinku, Habtamu; Tadesse, Fikir; Gedif, Azeb; Salah, Fekiahmed; Workie, Hailemariam Mekonnen (Frontiers in Nutrition, 2024)
BackgroundInadequate dietary diversity among children aged 6–23 months remains a public problem in Ethiopia. Adequate dietary diversity is crucial for children to meet their nutritional demands and promote healthy growth and development in infancy and young childhood.ObjectiveThe study aimed to assess dietary diversity and associated factors among children aged 6–23 months in Awi Zone, Ethiopia, 2023.MethodsThe study was conducted among children aged 6–23 months in Awi Zone, Amhara, Ethiopia, from August to September 2023. A community-based cross-sectional study design was conducted. A simple random sampling approach followed by face-to-face interview data collection techniques was used. To ascertain minimum dietary diversity, a 24 h food recall method comprising eight food item questionnaires was used. A statistical association was found between dependent and independent variables using the adjusted odds ratio with 95% confidence intervals and a p-value of ≤0.05.ResultThis study found that only 192 (47.6%) children aged 6–23-month old had adequate dietary diversity. In this study, variables such as maternal education [AOR 2.36, 95% CI (1.297, 3.957)], birth interval [AOR 2.85, 95% CI (1.45, 4.25)], and food insecurity [AOR = 2.23, 95% CI (1.626, 3.1)] were strongly significant variables for the minimum dietary diversity of the child.Conclusion and recommendationsThe proportion of the minimum dietary diversity was relatively low. Mother’s educational status, low birth intervals, and food insecurity were significant predictors of minimum dietary diversity. The stakeholders, including the Ministry of Health, regional health offices, and agricultural sectors, prioritize enhancing child nutrition through targeted food-based approaches. Developing and implementing comprehensive intervention programs to improve children’s minimum dietary diversity (MDD) should be a central focus. Professionals should strengthen nutrition education to promote optimal MDD practices.